The Effect of Basic Literacy Activity on the Fifth-Grade Elementary Students’ Reading Interest - Theresia Gulo; Rumiris Lumban Gaol; Patri Janson Silaban; Bogor Lumbanraja (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This study examines the effect of basic literacy activities on the reading interest of fifth-grade students at UPT SD Negeri 068008 Medan Tuntungan during the 2022/2023 academic year. A quantitative research design was employed to measure the relationship between literacy activities and students’ reading interest. The research population consisted of all 29 students in grade V, and a saturated sampling technique was applied, involving the entire VA class. Prior to the implementation of the literacy activities, students achieved an average reading interest score of 82.2, which falls within the moderate category. Data analysis indicated that the dataset was normally distributed, as shown by the normality test value of 0.936. Furthermore, the correlation analysis revealed a coefficient of 0.720, exceeding the critical value (rcount = 0.720 ≥ rtable = 0.367), leading to the acceptance of the alternative hypothesis. This result demonstrates a strong positive relationship between basic literacy activities and students’ reading interest. The significance of this relationship was further confirmed through a t-test analysis, where the calculated value (tcount = 5.391) exceeded the critical value (ttable = 1.703). These findings indicate that basic literacy activities have a statistically significant and positive effect on the reading interest of fifth-grade students at UPT SD Negeri 068008 Medan Tuntungan. Therefore, it can be concluded that the implementation of structured basic literacy activities plays an important role in fostering students’ reading interest at the elementary school level.